1996
DOI: 10.1021/la950616f
|View full text |Cite
|
Sign up to set email alerts
|

On the Composition of Sodium Taurodeoxycholate Micellar Solutions

Abstract: Composition and existence range of aggregates formed by sodium taurodeoxycholate in aqueous micellar solutions were studied. Electromotive force measurements provide the free concentration of hydrogen and sodium ions. Solubility measurements of barium taurodeoxycholate give that of taurodeoxycholate ions. Experimental data obtained at 25 °C and at seven different concentrations of N(CH3)4Cl, used as an ionic medium, can be explained by assuming the presence of aggregates with different composition depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
59
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 21 publications
10
59
1
Order By: Relevance
“…The same gel formation is favoured by high bile salt and hydrogen ion concentration. This conclusion agrees well with experiments carried out in previous researches 12,13 . The gel formation takes place more easily in TDC than in TC solutions.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The same gel formation is favoured by high bile salt and hydrogen ion concentration. This conclusion agrees well with experiments carried out in previous researches 12,13 . The gel formation takes place more easily in TDC than in TC solutions.…”
Section: Resultssupporting
confidence: 94%
“…From the protonation constants of the two investigated bile salts, it can be deduced that their protonation to form the corresponding acid takes place only at high hydrogen ion concentration (-log c H ≤ 2). Previously, it was found that the formation of protonated micellar species started at lower c H both for TDC (-log c H ≤ 7.5) and for TC (-log c H ≤ 4), respectively 12,13 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…An earlier investigation on solutions of NaTDC (Bottari and Festa, 1996) was carried out at 25 C and in N(CH 3 ) 4 Cl medium at seven different concentrations: 0.100, 0.200, 0.300, 0.400, 0.500, 0.600 and 0.750 mol dm À 3 . The results obtained at 0.500 mol dm À 3 were useful for taking into account the formation of aggregates between sodium and TDC, without calcium(II).…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of anions of some salts of dihydroxycholanic bile acids, like deoxycholate (DC -) (Bottari et al 1985;1989), glycodeoxycholate (GDC -) (Bottari and Festa, 1993) and taurodeoxycholate (TDC -) (Bottari and Festa, 1996) was studied previously.…”
Section: Introductionmentioning
confidence: 99%